Global Sea Ice Edge (netCDF) - Multimission ... : OSI-402-c ... - OSI SAF; EUMETSAT SAF On Ocean And Sea Ice (EUMETSAT SAF on Ocean and Sea Ice, 2017)
The Sea Ice Edge product is a classification product (open water/open ice/closed ice) and covers both the Northern and Southern Hemisphere. The sea ice edge is derived from passive microwave and active microwave sensors using a multi sensor methods with a Bayesian approach to combine the different sensors. ...